2018
DOI: 10.1787/9279f6c3-en
|View full text |Cite
|
Sign up to set email alerts
|

The drivers of regional growth in Russia

Abstract: This document, as well as any data and map included herein, are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area. 2 │ ECO/WKP(2018)71 DRIVERS OF REGIONAL GROWTH IN RUSSIA: A BASELINE MODEL WITH APPLICATION Unclassified OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Durand-Lasserve and Blöchliger (2018) find conditional beta-convergence over 2005-2015. Lehman et al (2020) exploit a modified version of conditional beta-convergence and also find convergence even over a longer period, 1996-2017 -in contrast to the earlier study, Lehmann and Silvagni (2013). Carvelli (2020) considers the period 1994-2015 and discovers that beta-convergence is accompanied by divergence in differences between the regional incomes and their sample average.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Durand-Lasserve and Blöchliger (2018) find conditional beta-convergence over 2005-2015. Lehman et al (2020) exploit a modified version of conditional beta-convergence and also find convergence even over a longer period, 1996-2017 -in contrast to the earlier study, Lehmann and Silvagni (2013). Carvelli (2020) considers the period 1994-2015 and discovers that beta-convergence is accompanied by divergence in differences between the regional incomes and their sample average.…”
Section: Introductionmentioning
confidence: 78%
“…Many of them use the regional GDP per capita as the income indicator, yielding contradictory results. Lehmann and Silvagni (2013), using data for 1995-2010 and betaconvergence, sigma-convergence, and distribution dynamics methodologies, find no evidence of convergence. Akhmedjonov et al (2013) test stationarity of the gap between regional and national GDP per capita in 2000-2008 for every region, thus deeming a common trend in these two series to be an indication of convergence.…”
Section: Introductionmentioning
confidence: 93%
“…The gains of Lithuania's globalising economy have concentrated in a few regions that have a qualified workforce and are well integrated in global value chains (Rusticelli and al, 2018 [1]). As many countries, Lithuania is converging towards the OECD average, while its individual parts are diverging (Bartolini, Stossberg and Blöchliger, 2016 [2]) (Bisciari, Essers and Vincent, 2020 [3]). Only four out of 60 municipalities registered population growth over the past decade, namely the largest cities and the resorts along the Baltic coast (Figure 2 A).…”
Section: Statlink 2 Https://doiorg/101787/888934185764mentioning
confidence: 99%
“…Nevertheless, there exist general robust findings which describe well the evolution of income disparities between the Russian regions, mainly measured by the beta-convergence models. Indeed, there is a clear common evidence for beta-divergence between the Russian regions during the first part of the transition period (Popov, 2001;Dolinskaya, 2002;Fedorov, 2002;Berkovitz & Dejong, 2002;Carluer, 2005;Benini et al, 2007;Badunenko et al, 2010) whereas evidence of beta-convergence has been found in the "Putin era" (Akhmedjonov, Chi, & Izgi, 2013;Oshchepkov, 2015) which in particular increased during the last decade (Vakulenko, 2016;Durand-Lasserve et al, 2018;Kaneva & Untura, 2019).…”
Section: Introductionmentioning
confidence: 99%